Mathematical HOTS cultivation via online learning environment and 5E inquiry model: cognitive impact and the learning activities - Ramlee, N. (Kassel University Press GmbH, 2019)
An ideal education is the one that enhance cognitive ability. In Malaysia, educators are currently putting enormous effort to uplift higher order thinking skills (HOTS) among students at various educational levels. The advancement of technology enables educators to apply online learning environment to further catalyze the effort. Integration of correct pedagogy is essential, 5E inquiry model by Bybee was implemented to 5E online learning environment-a learning environment developed for this research. The purpose of this research is to enhance HOTS among the samples. Thus, the cognitive impact of the learning environment was studied. The current gap of the learning activities that improve HOTS was addressed by probing into the activities done by samples. Samples are thirty-three secondary school students and had treatment with the learning environment for 4 weeks. T-test conducted found that samples' HOTS statistically significant higher after treatment compared to prior to the treatment, t (32) =-20.95, p < 0.05 that indicates the treatment improve samples' HOTS. The learning activities that materialize HOTS improvement is engaging learning module and HOTS related video. This research proves that human HOTS ability can be nurtured by using technology enhanced learning environment with the appropriate pedagogical approach. Deeper fundamental research regarding the process of learning that nurture HOTS is highly recommended in the future-one of the authors is currently working on.